Selection of biocontrol agents for control of onion white rot disease - Shehata, S. T.; Mosbah, M. M.; Hegazi, Late M. F. (2006)
Isolation of bioagents was carried out from rhizoplane of healthy onion plants, 70 and 120 days after transplanting from different governorates, i.e. EI-Behera; EISharkia; Beni-Swif and EI-Menia. Only 21 isolates from the obtained 331 isolates have prevented sclerotial formation of Sclerolium cepivorum on NYDA medium, The inhibition zones of mycelial growth of S. cepivorum after 14 days were 13,9,7,4 and 2 ml for isolates Pseudomonas flourescens; Bacillus licheniformis 10D14; Bacillus licheniformis 6D11; 7D12 and Chaetomium globosum respectively. Most of treatments of potting medium. with bacterial isolates soon after onion seeds sowin9, increased the percentage of onion seed germination. The highest increase 19.5 % was achieved by isolates B. licheniformis 6D11 and B. amyloliquefaciens 1D9. The promising biocontrol agents that had promotion toward onion seed germination and plant growth were tested in greenhouse for their potential control of onion white rot. At 50 or 100 sclerotia/ Kg potting medium, the best reduction in dead plants was achieved by treatment with P. flourescens, B. licheniformis 6D11. T. harzianum, B. amyloliquefaciens 1D9. C. globosum or Paenibacillus polymyxa 9014. Clear significant increase in plant height was occurred by treatment with P. flourescens followed by B. licheniformis 6D11. C. globosum, B. amyloliquefaciens 1D9, Trichoderma harzianum and Paenibacillus polymyxa 9014. However, in field expertment all applications were highly effective in reducing the percentage of dead onion plants due to white rot infection till the end of growing season (4.5 months from transplanting). The isolates, P. flourescens. B. licheniformis 6D11, B.amyloliquefaciens 1D9 or T. harzianum isolates were the most effective on disease control in the field. Significant increase in bulb yield was recorded with all tested isolates especially those of bacteria.
Includes references.
Summary in Arabic.
1
Keywords: White rot (Onions) -- Control; Phytopathogenic fungi -- Control; biological control